Metabolic syndrome and risk of subclinical hypothyroidism: a systematic review and meta-analysis - Zhong, Lei; Liu, Shuo; Yang, Yao; Xie, Tong; Liu, Jifeng; Zhao, Huahui; Tan, Guang (Frontiers in Endocrinology, 2024)
Background: Subclinical hypothyroidism (SCH) is a common endocrine subclinical disorder, the main adverse consequences of which are the development of clinical hypothyroidism and the promotion of ischemic heart disease. Metabolic syndrome (MetS) is a collection of metabolic problems. The goal of this meta-analysis was to evaluate the relationship between MetS and SCH.Methods: Suitable publications were identified using PubMed, Embase, and the Cochrane Library. The meta-analysis included only studies in English that reported odds ratio (OR) data for MetS and SCH.Two researchers combined data using a random-effects model. OR and 95% confidence intervals (CI) were used to present the results.Results: MetS was associated with an elevated risk of developing SCH (OR 2.56, 95% CI 1.44-2.55).However, the individual components of MetS were not associated with the risk of SCH. Subgroup analysis revealed that different definitions of MetS had varying effects on SCH. Sensitivity analysis confirmed that our results were robust.Conclusions: This meta-analysis indicates that patients with MetS have an increased risk of SCH, while there is no significant association between the five individual components of MetS and the risk of SCH.